Diabetes: What Challenges Lie Ahead for Vietnam? - Nguyen Bich Ngoc; Zhou Lu Lin; Waqas Ahmed (Ubiquity Press, 2020)
Background: Economic development and social environment changes influence disease patterns ranging from infectious diseases to noncommunicable diseases, and diabetes is one of the seven causes leading to death and disability in Vietnam. Objectives: The purpose of this research is to present an overview of the challenges related to diabetes prevention in Vietnam and to find effective ways for the prevention and control of diabetes, as well as to improve the quality of life among diabetes patients. Methods: The literature review was conducted using a variety of databases, such as PubMed, Google Scholar, Science Direct, Vietnamese data sources, and papers published in the Vietnamese language. For the searches, we used keywords such as "Diabetes," "Prevention," and "Prevalence of Diabetes." Findings and Conclusions: With the increasing prevalence of diabetes, there are approximately 5.76 million people with diabetes currently living in Vietnam. The age-adjusted comparative prevalence of diabetes in the population of Vietnam was approximately 6% in 2017. This review suggests that the government needs to establish social security and policy programs aimed at reducing social risk factors and the burden of healthcare costs for diabetes treatment in older people. In addition, attention should be paid to the management and control of diabetes-related diseases, with an emphasis on new techniques for early diagnosis and treatment. Simultaneously, the health system should ensure that diabetes patients living in rural areas and belonging to ethnic minorities can access better healthcare services to improve their health and decrease their risk for chronic disease and death.